2002
DOI: 10.1099/00221287-148-9-2661
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic switching and filamentation in Candida glabrata

Abstract: Candida glabrata switches spontaneously, reversibly and at high frequency among the following four phenotypes distinguishable by graded colony colouration on CuSO 4 -containing agar : white (Wh), light brown (LB), dark brown (DB) and very dark brown (vDB). These phenotypes also differ in a graded fashion in the level of expression of the metallothionein gene MTII (Wh T LB T DB a vDB), the frequency of switching (Wh S LB S DB S vDB) and colouration on phloxine B-containing agar (Wh S LB S DB S vDB). Switching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 43 publications
4
100
0
1
Order By: Relevance
“…Metallothionein production by switch phenotypes of C. glabrata was detected by the method described by Lachke et al (2002). Cells from a primary colony (cultured on RPMI agar containing 120 mg FL ml 21 ) and visually homogeneous for a single switch phenotype were inoculated into liquid yeast-peptone-glucose medium containing 1 mM CuSO 4 (YPG-CuSO 4 ) and grown at 25 uC until they reached a concentration of~5610 6 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallothionein production by switch phenotypes of C. glabrata was detected by the method described by Lachke et al (2002). Cells from a primary colony (cultured on RPMI agar containing 120 mg FL ml 21 ) and visually homogeneous for a single switch phenotype were inoculated into liquid yeast-peptone-glucose medium containing 1 mM CuSO 4 (YPG-CuSO 4 ) and grown at 25 uC until they reached a concentration of~5610 6 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…glabrata is known to switch to pseudohyphal growth when starved of nitrogen (Csank & Haynes, 2000), but the fungus does not form hyphae during host invasion (Lachke et al, 2002) and only budding growth has been observed in animal tissues (Fidel et al, 1999). In this study, highly FLresistant C. glabrata mutants formed a higher number of budding yeasts and also larger aggregates than the parental control when cultured in FCS, indicating that this attribute may be associated with high FL resistance.…”
Section: Induction Of Yeast Bud Formation and Co-aggregationmentioning
confidence: 99%
“…We previously demonstrated in limited plating experiments that 25 of 62 clinical isolates of C. glabrata (40 %) underwent core switching (Lachke et al, 2002). Strains that had not been observed to switch in the initial experiments did so in larger-scale plating experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The core phenotypes are white (Wh), light brown (LB), dark brown (DB) and very dark brown (vDB). Although core switching was first observed and defined on agar containing CuSO 4 , it has been shown to occur in the absence of CuSO 4 (Lachke et al, 2002) and can also be distinguished by graded pink coloration when grown on agar containing phloxine B (Lachke et al, 2002). Cells expressing any of the core phenotypes can also switch to the irregular wrinkle (IWr) phenotype, then back to the original core phenotype (Lachke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation